Post a New Question

calculus 1

posted by on .

differentiate x(x-3)^2

do I product and chain rule?

  • calculus 1 - ,

    f= uv
    f'=uv'+vu'

    f'= 1*(x-3)^2+ 2x(x-3)*1

  • calculus 1 - ,

    shouldn't it be 1 * (x-3)^2 + 2x(x-3)^1 ? instead of 2x(x-3) * 1 at the end?

  • calculus 1 - ,

    oh wait nvm i see what i did wrong

  • calculus 1 giyani high - ,

    x(x-3)^2
    =x(x-3)(x-3)
    =x(x^2-3x-3x+9)
    =x^3-6x^2+9x
    =3x^2-12x+9

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question